2023
DOI: 10.1093/alcalc/agad011
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Mental Health during the COVID-19 Pandemic

Abstract: Aims To examine the association between alcohol consumption and mental health during the COVID-19 pandemic. Methods An anonymous online survey was distributed among US adults during May–August 2020 through social networks and ResearchMatch. We collected information on demographic, lifestyles and mental health symptoms including anxiety, depression, stress and post-traumatic stress disorder. Logistic regression models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Increased alcohol consumption has been reported in other countries following the COVID‐19 pandemic 28–31 . Increased alcohol consumption has been reported to increase ORs for PTSD 32 . In Japan, national alcohol consumption decreased markedly in the 2021 fiscal year 33 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Increased alcohol consumption has been reported in other countries following the COVID‐19 pandemic 28–31 . Increased alcohol consumption has been reported to increase ORs for PTSD 32 . In Japan, national alcohol consumption decreased markedly in the 2021 fiscal year 33 .…”
Section: Discussionmentioning
confidence: 95%
“…[28][29][30][31] Increased alcohol consumption has been reported to increase ORs for PTSD. 32 In Japan, national alcohol consumption decreased markedly in the 2021 fiscal year. 33 In our study, approximately 11% of men showed an increase or decrease in this regard, whereas 8.9% of women showed an increase, with 12.6% showing a decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Also, some authors indicate up to a 22% reduction in the prescription of new antihypertensive medications in 2020 (Carr et al., 2022). Other potential explanations are related to sedentary behaviour, stress and distress, changes in daily life routine, or increased alcohol intake (Chambonniere et al., 2021; Yue et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, recently available studies identified a high prevalence of insomnia, stress, anxiety, depression, and trauma, along with other related psychological health problems, health behavior changes, and addictive issues among healthcare workers [2][3][4][5]. During the pandemic research evidenced that anxiety and depression contributed to increased alcohol consumption and heavy alcohol use exacerbated depression, anxiety, and insomnia, constituting a bidirectional association [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%